Edaphic fauna and residue decomposition rate under different management of plant species in no-tillage system - Polesso A.M. (2024)
© Akadémiai Kiadó Zrt. 2024.The no-tillage system (NTS) maximizes the use of plant species diversification during cultivation while minimizing disturbance to the seeding row and using the crop residues from previous species. Our objective was to compare management practices, including crop rotation (CR) and crop succession (CS), as well as a native fragment serving as a reference area (FC), and explore the relationship between litter decomposition and soil biological quality. To evaluate the decomposition of litter from soybean cultivation, we utilized fine (0.5 mm) and coarse (10 mm) mesh litter bags, which were placed in the soil and contained the winter crop residues. Additionally, sampling for edaphic fauna, microbiological, chemical, enzymatic, and environmental variables was conducted. A higher remaining mass was observed in the fine mesh litter bags (CR 75.5%, FC 68.3%, CS 63.9%) compared to the coarse mesh (FC 54.9%, CR 35.3%, CS 27.9%). Our results showed that diverse plant species composition led to a slower decomposition rate, similar to that found in native forests, stabilizing the agricultural system. Also, the decomposition rate was influenced by management practices, species selection, climate, and microbial activity. Epigeic invertebrates, particularly Detritivores/decomposers groups, played a significant role in litter decomposition, with higher decomposition rates observed in the coarse mesh. Microbial activity, influenced by soil attributes such as arylsulfatase enzyme activity, organic matter content, and soil moisture, significantly affected litter decomposition. The diversity of plant species in NTS increases the soil fauna and reduces litter decomposition rate. Therefore, we suggest NTS with CR using multiple plant species as a management that favors soil organisms in long-term systems.